Synergism between antibiotics and the extract of selected Prophet medicine toward different types of bacteria - Mohamed Ali, Insathe; Darnis, Deny Susanti (2014)
It is important to find new ways that are effective for the treatment of infectious diseases caused by drug-resistant bacteria such as the usage of plant extracts such as prophetic medicine which have the antibacterial activity together with antibiotics which do provide synergistic effect. The objectives of this study are to evaluate synergism between different types of prophetic medicine and antibiotics towards different bacterial strains and to increase the susceptibility of antibiotic resistant bacteria towards different types of antibiotics with the usage of Prophetic medicine. Three samples of Prophetic medicine had been used such as Allium Cepa (Onion), Aloe Vera (Aloe) and Ocimum basilicum (Basil) was prepared by the method freeze drying. Those samples are combined with several types of antibiotics like ampicillin, erythromycin, penicillin, streptomycin and tetracycline and were tested against different types of bacteria which are S.aureus, B.cereus, E.coli and P.aeruginosa by using broth microdilution method in order to determine the minimum inhibitory concentration (MIC). Fractional inhibitory concentration (FIC) was determined in order to know the synergy interaction between the prophetic medicine and antibiotics. The antibiotic penicillin produces synergistic effect when being combined with onion in order to combat the bacteria S.aureus, B.cereus and E.coli. The combination between onion and both ampicillin and erythromycin also have synergism toward overcoming the bacteria E.coli. Other than that combination of basil with both ampicillin and penicillin also produces synergistic effect upon combating B.cereus while, for aloe it produces synergism when being combined with tetracycline and penicillin in order to combat the bacteria S.aureus and E.coli respectively. Most of the effect of synergism observed when prophetic medicine was given with the antibiotic penicillin. Hence it can be concluded that only certain Prophetic Medicine can provide synergistic effect with certain types of antibiotic in order to combat a particular bacteria due to their different ways of combating the bacteria and only antibacterial activity of both at the same place will have synergistic effect.